Cognitive Impairment in Bipolar Disorder and Schizophrenia: A Systematic Review - Vöhringer, Paul A.; Barroilhet, Sergio; Amerio, Andrea; Reale, Maria L.; Vergne, Derick; Alvear, Katherine; Ghaemi, S N. (Frontiers in Psychiatry, 2013)
AIMS: Previous comparisons of cognitive decline among patients with bipolar disorder and schizophrenia have found somehow quite similar profiles of deficits, but results have varied between studies. Therefore an extensive and thoughtful systematic review of the matter is warranted. METHODS: Studies were found through systematic search (PubMed) following PRISMA guidelines. To be included, studies must have assessed the following cognitive functions: executive functions, memory, IQ, attention-concentration and perceptuomotor function. In order to make comparison between the two entities, studies should include bipolar disorder patients with operationally defined euthymia, schizophrenic patients in remission, and third group of healthy control patients. Comparisons were made after controlling for years of schooling and residual affective symptoms. RESULTS: We found that overall both SZ and BD patients present deficits on all neurocognitive measures compared to healthy controls (HC). In particular, SZ patients show more severe and pervasive cognitive deficits while BD patients present a milder and more confined impairment. In addition, evidence from the literature suggests that SZ and BD patients share a similar cognitive impairment profile with different degrees of deficits. Therefore, the difference between the two groups seems to be more quantitative (degree of deficit) rather than qualitative (profile), supporting a dimensional approach to the two clinical entities. Limitations of the present review includes the impossibility to control for effects of medication, varying time required for assessment across studies, illness diagnosis reliability and course severity CONCLUSIONS: Patients with bipolar disorder might exhibit a cognitive impairment that could be similar to schizophrenia in terms of their profile, although patients with schizophrenia may have more severe and widespread impairments.